Borate-treated strand board from southern wood species: Resistance against decay and mold fungi - Xinwu Xu (BioResources, 2013)
Combined decay and mold resistance of zinc borate-(ZB) and calcium borate-(CB) treated oriented strand board (OSB) from southern mixed hardwood (MHW) and southern yellow pine (SYP) was investigated. Tests were done with a brown-rot fungus, Gloeophyllum trabeum, and a white-rot fungus, Trametes versicolor, for 8 and 12 weeks, respectively. Wood species and fungus type had significant influence on the decay resistance. Decay caused by the brown-rot fungus was evident for all untreated SYP and mixed MHW controls. White-rot fungus did not cause significant sample weight loss for either species group. In the SYP OSB control inoculated with G. trabeum, the hyphae were abundant in wood rays and cell walls where they primarily penetrated through bordered and simple pits. The incorporation of ZB and CB into OSB provided significant protection against the fungi with no significant weight loss observed in the treated OSB. Microscopic analysis showed distinct evidence of fungal colonization and a thinning pattern of cell wall material. Untreated OSB samples from MHW and commercial OSBs were most susceptible to mold growth after 6 weeks. The borate-modified OSB from MHW and SYP effectively prevented the mold growth.